INVESTIGATING THE APPOINTMENT SCHEDULING SYSTEM AT DENTAL CLINIC USING GREEDY HEURISTICS - Mat Desa, Wan Laailatul Hanim; Abdul Rahman, Rosshairy; Hwei, Lau Ying; Fung, Yong Choy (Journal of Technology Management and Business, 2018)
This study was designed to discuss the application of job shop scheduling with greedy technique to investigate the total time delayed for completing the dental treatment in the dental clinic. The aim of this study is to identify the total number of patients delayed for completing the dental treatment as scheduled per day. Besides, this study also aims to examine the solution obtained from each greedy technique. There are three greedy techniques have been employed which are the earliest due date, shortest processing time and longest processing time. The result of the investigation indicated that the techniques of the earliest due date and shortest processing time provide optimal solution with no delays. It is shows that the solution from this study can be used as a guideline of patient scheduling in any related application.Keywords: appointment, job shop scheduling, dental clinic, number of patients delayed, total time delayed